Glutathione-S-transferase: a minor allergen in birch pollen due to limited release from hydrated pollen. - Stephan Deifl (PLoS ONE, 2014)
Recently, a protein homologous to glutathione-S-transferases (GST) was detected in prominent amounts in birch pollen by proteomic profiling. As members of the GST family are relevant allergens in mites, cockroach and fungi we investigated the allergenic relevance of GST from birch (bGST).bGST was expressed in Escherichia coli, purified and characterized by mass spectrometry. Sera from 217 birch pollen-allergic patients were tested for IgE-reactivity to bGST by ELISA. The mediator-releasing activity of bGST was analysed with IgE-loaded rat basophil leukaemia cells (RBL) expressing human FcεRI. BALB/c mice were immunized with bGST or Bet v 1. Antibody and T cell responses to either protein were assessed. IgE-cross-reactivity between bGST with GST from house dust mite, Der p 8, was studied with murine and human sera in ELISA. The release kinetics of bGST and Bet v 1 from birch pollen were assessed in water, simulated lung fluid, 0.9% NaCl and PBS. Eluted proteins were quantified by ELISA and analysed by immunoblotting.Only 13% of 217 birch pollen-allergic patients showed IgE-reactivity to bGST. In RBL assays bGST induced mediator release. Immunization of mice with bGST induced specific IgE and a Th2-dominated cellular immune response comparably to immunization with Bet v 1. bGST did not cross-react with Der p 8. In contrast to Bet v 1, only low amounts of bGST were released from pollen grains upon incubation in water and the different physiological solutions.Although bGST is abundant in birch pollen, immunogenic in mice and able to induce mediator release from effector cells passively loaded with specific IgE, it is a minor allergen for birch pollen-allergic patients. We refer this discrepancy to its limited release from hydrated pollen. Hence, bGST is an example demonstrating that allergenicity depends mainly on rapid elution from airborne particles.